2018
DOI: 10.1016/j.envres.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The association between ambient temperature and mortality in South Africa: A time-series analysis

Abstract: BackgroundThere is an extensive literature describing temperature-mortality associations in developed regions, but research from developing countries, and Africa in particular, is limited.MethodsWe conducted a time-series analysis using daily temperature data and a national dataset of all 8.8 million recorded deaths in South Africa between 1997 and 2013. Mortality and temperature data were linked at the district municipality level and relationships were estimated with a distributed lag non-linear model with 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
84
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 46 publications
15
84
0
1
Order By: Relevance
“…We found seasonal changes in the prevalence of respiratory conditions and of tail biting at the national level which is in agreement with previous analyses [10,11,15,22,26,29,30]. The association between ambient temperature and mortality in both humans and animals has been reported to fit a J-or U-shaped curve, with extreme temperatures being linked with increased mortality [31][32][33][34][35] and respiratory morbidity [36]. In this study, the relationship with outcomes was better described by an A-shaped curve in the national dataset, with inconsistent patterns displayed across the county-level datasets.…”
Section: Previous Studiessupporting
confidence: 91%
“…We found seasonal changes in the prevalence of respiratory conditions and of tail biting at the national level which is in agreement with previous analyses [10,11,15,22,26,29,30]. The association between ambient temperature and mortality in both humans and animals has been reported to fit a J-or U-shaped curve, with extreme temperatures being linked with increased mortality [31][32][33][34][35] and respiratory morbidity [36]. In this study, the relationship with outcomes was better described by an A-shaped curve in the national dataset, with inconsistent patterns displayed across the county-level datasets.…”
Section: Previous Studiessupporting
confidence: 91%
“…In addition to physiological acclimatization, the socioeconomic conditions can affect human's behavioural and technological adaptations to ambient temperature. Some studies have confirmed the conclusion 24,30 .…”
Section: Discussionmentioning
confidence: 78%
“…A total of 210 papers investigated the relationships between daily temperature and human mortality counts for non-external causes using the DLNM method. Excluding the literature from the repeated study areas, 16 papers 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] of which are chosen. These studies involved 420 locations from 30 countries, covering six continents (Antarctica was excluded).…”
mentioning
confidence: 99%
“…Though several studies predict that global warming will lead to an increase in heat-related mortality and a decrease in cold-related mortality in the future, only a few consider minimum mortality temperature (MMT) as a reference value to estimate future relative risks or attributable mortality [1,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%